2015
DOI: 10.1080/10538720.2015.988837
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Reality With Fantasy: Exploration of the Sociocultural Factors Influencing HIV Transmission Among Black Young Men Who Have Sex With Men (BYMSM) Within the House Ball Community: A Chicago Study

Abstract: Studies involving the House Ball Community (HBC) have found high rates of HIV prevalence and undiagnosed HIV infection, as well as unique social and sexual network-related HIV risk and protective behaviors (Murrill et al., 2008; Sanchez et al., 2010). Efforts to understand culturally-appropriate and effective methods of HIV prevention services within the relatively understudied HBC are scarce (Phillips et al., 2011). This qualitative study, utilizing a Diffusion of Innovation Theoretical framework, aimed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…First, to our knowledge, this analysis is the first to adopt a comparative approach to ascertaining the extent to which houses and families offer YBMSM added protection. While prior studies of the house and ballroom communities in cities like Chicago (Lemos et al, 2015), Los Angeles (Holloway, Schrager, Wong, Dunlap, & Kipke, 2014; Kubicek et al, 2013), New York (Murrill et al, 2008) and Philadelphia (Castillo et al, 2012) have identified and investigated practices and behaviors within these settings that span the protective-risk spectrum, little to no work has compared the prevalence of these traits to what exists in the non-affiliated YBMSM community. In taking this step, we develop a clearer picture of intra-population differences and the added value that houses and families introduce into the lives of its members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, to our knowledge, this analysis is the first to adopt a comparative approach to ascertaining the extent to which houses and families offer YBMSM added protection. While prior studies of the house and ballroom communities in cities like Chicago (Lemos et al, 2015), Los Angeles (Holloway, Schrager, Wong, Dunlap, & Kipke, 2014; Kubicek et al, 2013), New York (Murrill et al, 2008) and Philadelphia (Castillo et al, 2012) have identified and investigated practices and behaviors within these settings that span the protective-risk spectrum, little to no work has compared the prevalence of these traits to what exists in the non-affiliated YBMSM community. In taking this step, we develop a clearer picture of intra-population differences and the added value that houses and families introduce into the lives of its members.…”
Section: Discussionmentioning
confidence: 99%
“…One strand focuses on the prevalence of HIV and other related risk factors in the community. In general, these studies note high rates of seroprevalence, lower rates of testing, engagement in condomless sex, as well as practices like age-discordant coupling and exchange sex that increase exposure to risk (Castillo, Palmer, Rudy, & Fernandez, 2012; Lemos, Hosek, & Bell, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…however, house leaders noted that regular partners change frequently with youth experiencing multiple sexual partner (Lemos et al, 2015). In addition, the study found that exchange sex increased HIV risk and that youth were paid more for condomless sex (Lemos et al, 2015).…”
Section: Study-specific Findingsmentioning
confidence: 87%
“…This community often engages in specific behaviors resulting in an increased risk (Olivas, et al 2019) Exploring Health and Wellbeing in the US House Ball Community: A Systematic Review for HIV infection, such as alcohol and drug abuse, unprotected sex, and exchange sex (Dickson-Gomez et al, 2014;Kipke, Kubicek, Supan, Weiss, & Schrager, 2013;Murrill et al, 2008;Phillips, Peterson, Binson, Hidalgo, & Magnus, 2011;Sanchez, Finlayson, Murrill, Guilin, & Dean, 2010;Schrager, Latkin, Weiss, Kubicek, & Kipke, 2014). Lemos et al (2015) found that some members of the HBC engaged in sexual risk behaviors as a way of gaining acceptance and obtaining social status embedded in the social norms of the HBC. A large study of the HBC in New York City found that HIV testing within the community was approximately 60% for the previous 12 months, and among those 17% tested positive with 75% unaware of their positive status (Murrill et al, 2008).…”
Section: Introductionmentioning
confidence: 99%